DISTINGUISH ERRORS IN STUDENTS FINAL ORAL TEST OF PHONOLOGY CLASS - Syaputri, Wuri (JURNAL SMART, 2015)
AbstractÂ The objectives of the study were finding the types of errors were made by the students in the final oral testand the causes of the errors. The method was using descriptive approach which concern in descriptive qualitative technique. The data collection method was using observation and interview. The steps of the data analysis were recording the studentâs spoken, transcribing, eliminating, identifying, composite report. The result showed that the students gaps of the score because of three errors. They were pre systematic, systematic and post systematic errors. Those errors were affected by three causes. They were interference, intralingual and developmental.Â Keywords: Errors, Oral Test, Phonology